Analysis of Screen Based Activity on Digital Eye Strain in School-Age Children in Peniwen Village, Malang, East Java - Minarni Wartiningsih (Asian Journal of Health Research, 2023)
Introduction: The use of digital devices has increased across all age groups and professional fields, making them inseparable from everyday life. This increase in the duration of screen-based activities causes various symptoms of eye health problems. This study aimed to determine the prediction of the relationship and influence between Screen-Based Activity (SBA) and the incidence of Digital Eye Syndrome (DES) in children aged 9-12 years in Peniwen Village, Malang. Material and Methods: This study used a cross-sectional analytical observational design. There were 62 respondents in the research samples, or the same number as the total population. The analysis technique used in this study is the Partial Leas Square (PLS) modeling technique with testing using software such as SmartPLS (v3.2.9). Results: Based on the results of the analysis, obtained t-count (23.821) is greater than the t-table (1.96), meaning that there is a relationship and influence between SBA variables on DES. The correlation coefficient of SBA to DES is positive 0.818 which means the higher the Screen Based Activity, the higher the risk of Digital Eye Strain. The use of handphone (X2) is an indicator of SBA with the highest correlation strength of 88.1%. Conclusion: There is an association between the duration of Screen Based Activity and the incidence of Digital Eye Strain in children. The higher the Screen Based Activity, the higher the risk of Digital Eye Strain. In addition, the use of handphones has the highest correlation in influencing the occurrence of Digital Eye Strain in school-age children in Peniwen Village.